Effectiveness Analysis of Thematic Tafsir-Based Maharah Qira’ah Learning Materials for Students Memorizing the Qur’an - Iqbal Akmalun Ni'am; Nurul Murtadho; Moh. Ainin; Umi Machmudah (UIN Syekh Wasil Kediri, Indonesia, 2025)
In the context of Islamic boarding school (pesantren) education, the skill of memorizing the Qur’an is often not accompanied by an adequate understanding of its meaning. One promising approach to address this issue is the integration of Maharah Qira’ah (reading skills) with thematic Qur’anic interpretation (tafsir tematik). This study aims to analyze the effectiveness of a Maharah Qira’ah teaching material based on thematic interpretation that was previously developed for students who have memorized the Qur’an (santri penghafal Al-Qur’an). This research employed a quantitative approach using a pre-experimental design with a one-group pre-test and post-test model. The research subjects consisted of 10 Qur’an-memorizing students from an Islamic boarding school in East Java. The instruments included pre-test and post-test assessments, supplemented by observation and field notes as supporting data. Data were analyzed using a paired sample t-test with the assistance of SPSS software. The results showed a significant increase in the mean score from 76.0 to 97.0 after the use of the teaching material, with a significance value of 0.004 (p < 0.05). The decrease in standard deviation from 16.47 to 4.83 indicates improved equality in student learning outcomes. These findings demonstrate that the thematic tafsir-based Maharah Qira’ah material is effective in enhancing students’ contextual understanding of Qur’anic verses. Therefore, this teaching material can serve as an innovative alternative for reading instruction among Qur’an-memorizing students, as it successfully integrates memorization with comprehension through a thematic and real-life context-based approach. Abstrak: Dalam konteks pendidikan pesantren, keterampilan menghafal Al-Qur’an belum sepenuhnya diimbangi dengan kemampuan memahami isi kandungannya. Salah satu pendekatan yang berpotensi mengatasi permasalahan ini adalah pembelajaran Maharah Qiraah berbasis tafsir tematik. Penelitian ini bertujuan untuk menganalisis efektivitas bahan ajar Maharah Qiraah berbasis tafsir tematik yang telah dikembangkan sebelumnya untuk santri penghafal Al-Qur’an. Penelitian ini menggunakan pendekatan kuantitatif dengan metode pre-experimental design tipe one group pre-test and post-test. Subjek penelitian adalah 10 santri penghafal Al-Qur’an dari salah satu pesantren di Jawa Timur. Instrumen yang digunakan meliputi tes awal dan tes akhir, serta observasi dan catatan lapangan sebagai data pendukung. Analisis dilakukan menggunakan uji paired sample t-test dengan bantuan program SPSS. Hasil penelitian menunjukkan peningkatan signifikan nilai rata-rata dari 76,0 menjadi 97,0 setelah penggunaan bahan ajar, dengan nilai signifikansi sebesar 0,004 (p < 0,05). Penurunan standar deviasi dari 16,47 menjadi 4,83 menunjukkan adanya peningkatan pemerataan hasil belajar. Temuan ini menunjukkan bahwa bahan ajar Maharah Qiraah berbasis tafsir tematik efektif meningkatkan pemahaman santri terhadap makna ayat-ayat Al-Qur’an secara kontekstual. Dengan demikian, bahan ajar ini dapat menjadi alternatif inovatif dalam pembelajaran membaca bagi penghafal Al-Qur’an, karena mampu menggabungkan aspek hafalan dengan pemahaman melalui pendekatan tematik dan berbasis konteks kehidupan nyata.